Black-Gloss Campana Pottery from Nikonion and Histria – Preliminary Study - Głuszek, Inga (Acta Archaeologica Lodziensia, 2019)
The archaeological excavations on ancient archaeological sites of North-western coast of the Black Sea have brought a great number of finds of black-gloss pottery. For pottery examples dated on the Archaic and Classical periods, these are mainly vessels manufactured in Athens. In contrast, artefacts from the Hellenistic period represent a wide spectrum of imports from various centres of production. At the current stage of research, many production centres have not yet been recognized. However the dynamically developing studies in this area allowed to recognised a several centres of production such as Pergamon, Knidos, Thasos workshops as well as the Asia Minor group. These groups of pottery were recognised among archaeological finds from the north-western Black Sea territory. Considering the black-gloss pottery from that region the appearance of the Campana ware is very interesting and suggests a wide range of long distance distribution of tableware in the Hellenistic period.